Hubungan Antara Tayangan Youtube Sorabel dengan Pemenuhan Kebutuhan Informasi Warganet: Studi Korelasional pada Akun Media Sosial Youtube Sorabel - Dena Delaeni; Neni Yulianita (Bandung Conference Series: Public Relations, 2022)
Abstract. Social media is an online media that is used by users to represent themselves or interact, cooperate, communicate, share with other users, thus forming social bonds virtually. One of the social media that still has many visitors today is Youtube. Youtube is one of the sites that is widely used by audiences to find various kinds of information, especially in terms of fashion. One of the YouTube channels that discusses fashion is Sorabel. The purpose of this study is to find and analyze whether there is a relationship between the type of media, media content, and the exposure of Sorabel's Youtube show media with the fulfillment of netizens' information needs. The theory used in this study is the theory of uses and gratifications. The method used in this study is the correlational method. The sampling technique used in this study was simple random sampling. The population and samples taken by the researchers were netizens who watched and commented in one of Sorabel's Youtube shows entitled "Tips for Accurately Matching Clothes Colors" which totaled 83 people. The results of the study found that the entire hypothesis tested got the results of Ho rejected which means that there is a relationship between the type of media, media content and the exposure of Sorabel's Youtube show media with the fulfillment of netizens' information needs. Abstrak. Media sosial adalah sebuah media online yang digunakan pengguna sebagai merepresentasikan dirinya maupun berinteraksi, bekerja sama, berkomunikasi, berbagi dengan pengguna lain, sehingga membentuk ikatan sosial secara virtual. Salah satu media sosial yang hingga kini masih memiliki banyak pengunjung adalah youtube. Youtube merupakan salah satu situs yang banyak digunakan khalayak untuk mencari berbagai macam informasi, terutama dalam hal fashion. Salah satu channel youtube yang membahas mengenai fashion adalah Sorabel. Tujuan penelitian ini adalah untuk menemukan dan menganalisis apakah terdapat hubungan antara jenis media, isi media, dan terpaan media tayangan Youtube Sorabel dengan pemenuhan kebutuhan informasi warganet. Teori yang digunakan dalam penelitian ini adalah teori uses and gratifications. Metode yang digunakan dalam penelitian ini adalah metode korelasional. Teknik sampling yang digunakan dalam penelitian ini adalah simple random sampling. Populasi dan sampel yang diambil oleh peneliti adalah warganet yang menonton dan berkomentar dalam salah satu tayangan Youtube Sorabel yang berjudul “Tips Jitu Padu Padan Warna Pakaian” yang berjumlah 83 orang. Hasil penelitian diketahui bahwa keseluruhan hipotesis yang diuji mendapatkan hasil Ho ditolak yang berarti terdapat hubungan antara jenis media, isi media dan terpaan media tayangan Youtube Sorabel dengan pemenuhan kebutuhan informasi warganet.